Treatment patterns and clinical profile in progressive pulmonary fibrosis: a Japanese cross-sectional survey - Yasuoka, Hidekata; Waseda, Yuko; Kaneko, Yuko; Okazaki, Masateru; Iwasaki, Ryoko; Nagata, Shoko; Small, Mark; Ishii, Haruyuki (Frontiers in Medicine, 2025)
BackgroundThere is a paucity of real-world data on patients with interstitial lung diseases (ILDs) that are progressive, other than idiopathic pulmonary fibrosis (IPF), including treatment patterns and attitudes toward treatment. This study aimed to investigate the diagnosis, clinical characteristics, treatment paradigm and current decision-making practices of IPF and progressive pulmonary fibrosis (PPF) in a Japanese real-world setting.MethodsData were drawn from the Adelphi Real World PPF-ILD Disease Specific Programme™, a cross-sectional survey with retrospective data collection of pulmonologists and rheumatologists in Japan from April to October 2022. Physicians provided data for up to 12 consecutive patients with a physician-confirmed diagnosis of progressive ILD; patients were also invited to complete patient self-completion forms. Analyses were descriptive.ResultsA total of 63 physicians (43 pulmonologists and 20 rheumatologists) provided data on 312 patients with PPF and 70 patients with IPF. Patients had a mean (standard deviation [SD]) age at survey date of 68.0 (11.6) years, 43.5% were female, 50.3% were former smokers and 18.1% were employed full time. For breathlessness, 26.5% of patients had Grade 2 physician-reported breathlessness; this was 16.7% when reported by patients themselves. A total of 81.4% of patients were currently receiving treatment for ILD. Mean (SD) duration of current treatment was 1.5 (1.4) years. Slowing disease progression was the primary reason influencing physicians’ choice of current ILD treatment (48.5%). A total of 16.0% had never been treated (most frequent physician-reported reason: disease was manageable without treatment, 55.7%) and 2.6% had treatment discontinued (most frequent reason: patient request, 70.0%). Physicians reported 82.3% of patients as fully compliant with their treatment regimen. As reported by patients themselves (n = 53), 49.1% never and 37.7% rarely missed a dose.ConclusionThis analysis of real-world data from Japan provides insights into the clinical profile of patients with IPF and PPF in Japan, and highlights differences between physicians and patients in perception of symptom severity and attitudes to treatment.